Analysis of flow structures in cavity flow with modifications to cavity geometry - Pey, Yin Yin (2014)
Flow over cavity exists in a wide range of flow phenomena and remains a challenging problem till today. The objective of this study is to investigate the physics of cavity flow in response to trailing edge modifications. Trailing edge ramps were selected as the passive control method to be studied as they have the potential to reduce high pressure impacts caused by the impingement of shear layer.